CLINICO-PATHOLOGICAL FEATURES, OCCUPATIONAL RISK FACTORS AND LIFE STYLE IN THE PATIENTS OF CERVICAL CANCER - Balbir Singh; Vigyan Singh; Dwijendra Nath; Ramesh Kumar (International Journal of Pharmacy with Medical Sciences, 2026)
The incidences of cervical cancer nowadays, have shown higher occurrence rate in women belonging to very low socio-economic status as well as residing in unhygienic conditions especially in rural and slum areas. Recently, due to application of various effective screening methods, health care and survey programme conducted in Western countries, due to which the incidence of invasive cervical cancer have been decreased. In spite of effective screening techniques, still cervical cancer remain one of the most common cancer in women, next to breast and lung cancer, which is most leading cause of female patients death in India. Most prevevalent states in India… The various associated risk factors are multiple sexual partners, high-risk male whose previous partner had cervical cancer and persistent HPV infection, lower socio-economic status, multiple pregnancies, promiscuity, exposure to carcinogens, smoking and long term oral contraceptive pills (OCP) usage. In this present study, we observed a strong association is found between clinico-pathological features, occupational, life style and risk of developing cervical cancer in individuals carrying specific alleles among the population 18,19 .